Diagnosis and treatment of chronic inflammatory demyelinating polyradiculoneuropathy in clinical practice: A survey among Dutch neurologists. Issue 3 (9th July 2020) - Broers, Merel C.; van Doorn, Pieter A.; Kuitwaard, Krista; Eftimov, Filip; Wirtz, Paul W.; Goedee, Stephan; Lingsma, Hester F.; Jacobs, Bart C.
Abstract: The diagnosis and treatment of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is often a challenge. The clinical presentation is diverse, accurate biomarkers are lacking, and the best strategy to initiate and maintain treatment is unclear. The aim of this study was to determine how neurologists diagnose and treat CIDP. We conducted a cross‐sectional survey on diagnostic and treatment practices among Dutch neurologists involved in the clinical care of CIDP patients. Forty‐four neurologists completed the survey (44/71; 62%). The respondents indicated to use the European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) 2010 CIDP guideline for the diagnosis in 77% and for treatment in 50%. Only 57% of respondents indicated that the presence of demyelinating electrophysiological findings was mandatory to confirm the diagnosis of CIDP. Most neurologists used intravenous immunoglobulins (IVIg) as first choice treatment, but the indications to start, optimize, or withdraw IVIg, and the use of other immune‐modulatory therapies varied. University‐affiliated respondents used the EFNS/PNS 2010 diagnostic criteria, nerve imaging tools, and immunosuppressive drugs more often. Despite the existence of an international guideline, there is considerable variation among neurologists in the strategies employed to diagnose and treat CIDP. More specific recommendations regarding: (a) the minimal set of electrophysiological requirements to diagnose CIDP, (b) the possible added value of nerve imaging, especially in patients not meeting the electrodiagnostic criteria, (c) the most relevant serological examinations, and (d) the clear treatment advice, in the new EFNS/PNS guideline, would likely support its implementation in clinical practice.